2007
DOI: 10.2337/db06-1100
|View full text |Cite
|
Sign up to set email alerts
|

The SUMO Conjugating Enzyme Ubc9 is a Regulator of GLUT4 Turnover and Targeting to the Insulin-Responsive Storage Compartment in 3T3-L1 Adipocytes

Abstract: The small ubiquitin-related modifier (SUMO) conjugating enzyme Ubc9 has been shown to upregulate GLUT4 in L6 myoblast cells, although the mechanism of action has remained undefined. Here we investigated the physiological significance of Ubc9 in GLUT4 turnover and subcellular targeting by adenovirus vector-mediated overexpression and by small interfering RNA (siRNA)-mediated gene silencing of Ubc9 in 3T3-L1 adipocytes. Overexpression of Ubc9 resulted in an inhibition of GLUT4 degradation and promoted its target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 33 publications
2
72
1
Order By: Relevance
“…This model is consistent with previous observations that insulin accelerates GLUT4 turnover (4) and that prolonged insulin stimulation reduces GLUT4 by a de novo protein synthesis-independent mechanism (38). On the other hand, because TGN is the most likely compartment for the generation of insulin-sensitive GLUT4 pool(s) (41,42), retromer-mediated retrograde transport of GLUT4 may be critical for the generation of an insulin-sensitive pool (43), and insulin-elicited switching of GLUT4 sorting at the endosomes may partly explain the inverse correlation between GLUT4 turnover and its targeting to GSC or biogenesis of the insulin-responsive GLUT4 vesicles (7,24). A recent proteomic analysis of GLUT4 vesicles (44) has shown that the insulin-responsive GLUT4 vesicles contain retromer components such as Vps35 and Vps26 as well as retromer cargo proteins including the mannose 6-phosphate receptor, sortilin, and sortilin-related LDL receptor relative 11 (SorLA).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This model is consistent with previous observations that insulin accelerates GLUT4 turnover (4) and that prolonged insulin stimulation reduces GLUT4 by a de novo protein synthesis-independent mechanism (38). On the other hand, because TGN is the most likely compartment for the generation of insulin-sensitive GLUT4 pool(s) (41,42), retromer-mediated retrograde transport of GLUT4 may be critical for the generation of an insulin-sensitive pool (43), and insulin-elicited switching of GLUT4 sorting at the endosomes may partly explain the inverse correlation between GLUT4 turnover and its targeting to GSC or biogenesis of the insulin-responsive GLUT4 vesicles (7,24). A recent proteomic analysis of GLUT4 vesicles (44) has shown that the insulin-responsive GLUT4 vesicles contain retromer components such as Vps35 and Vps26 as well as retromer cargo proteins including the mannose 6-phosphate receptor, sortilin, and sortilin-related LDL receptor relative 11 (SorLA).…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture and Differentiation-3T3-L1 cells provided by Howard Green (Harvard Medical School, Boston, MA) (17) were maintained in Dulbecco's modified Eagle's medium containing 4.5 g/liter D-glucose supplemented with 10% calf serum and differentiated into adipocytes in DMEM containing 1.0 g/liter D-glucose (DMEM-LG) supplemented with 10% fetal bovine serum (FBS) as described previously (7).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations